WANITA PENDULANG EMAS DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI KELUARGA - Deffrinica deffrinica; Benenitkha Kikky Vuspitasari; Amanda Okta Karolina (Universitas Sang Bumi Ruwa Jurai, 2020)
This research was conducted in Bengkayang West Kalimantan which aims to describe: 1. The income of female gold panning workers, 2 to see the contribution of household income of women who pan gold, 3. See the role of the involvement of women who pan gold in improving the economic welfare of the family. This research type is descriptive qualitative. The population of this study were 10 gold panning women. Data collected through direct interviews with respondents. The results of this study indicate that the economic activities carried out by women who pan gold miners provide income that can meet the needs of women's gold panning households. And the contribution made by women who pan gold in improving the economy of family welfare, amounting to 3,000,000-22,500,000 / month in Bengkayang is quite large towards the income of women who pan gold.